Effect of Valsalva Maneuver on Choriocapillary Retinal Microvasculature - Wiest, Maximilian Robert Justus; Hamann, Timothy; Zweifel, Sandrine (Klinische Monatsblätter für Augenheilkunde, 2022)
Purpose We aimed to identify and evaluate possible quantitative changes in retinal and choriocapillary blood flow utilizing optical coherence tomography angiography (OCTA) imaging in healthy study subjects during the Valsalva maneuver (VM).Methods OCTA imaging with a ZEISS PlexElite 9000 on one eye was performed. OCTA images were acquired before VM and 5 seconds after. Images were segmented and underwent projection removal using algorithms supplied by the manufacturer. Analysis of vessel density (VD) and vessel length density (VLD) were performed on superficial (SCP) and deep capillary plexus (DCP) layer slabs using ImageJ. ImageJ was also utilized for analyzing flow voids (FVs) in the choriocapillary slabs.Results Ten (8 right, 2 left) eyes of 10 (5 male, 5 female) healthy study subjects were included. Pre-VM, -VD, and -VLD were 0.428 (± 0.291) and 17.871 mm−1 (± 2.22 mm−1) in the SCP and 0.423 (± 0.0213) and 23.850 mm−1 (± 1.023 mm−1) in the DCP. Pre-VM and -FV were measured at 19.686 (± 1.959). During VM, VD, and VLD in the SCP were 0.417 (± 0.024) and 17.376 mm−1 (± 2.007 mm−1), and in the DCP, 0.426 (± 0.221) and 23.944 mm−1 (± 1.021 mm−1), respectively. FV post-VM was 20.440 (± 2.062). A paired samples t-test test revealed no significant changes in any of the observed parameters.Conclusion We did not observe any significant changes in the VD, VLD, or FV. This might be due to autoregulatory processes in the ocular vasculature. Due to the small sample size, confidence intervals are comparatively large. Further study with more probands might yield different results.
Keywords: Valsalva maneuver; ocular physiology; medical retina; multimodal imaging; optical coherence tomography angiography